(untitled) (Medical Forum Monthly, 2023)
Objective: This study was undertaken to see the value of GeneXpert MTB Rif Assay in diagnosing the TB among suspicious household contacts and its incremental yield over smear microscopy and x-ray. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Department of Pulmonology, Bahawal Victoria Hospital, Bahawalpur from January 2017 to December 2022. Materials and Methods: Systemic tool for active TB case detection was followed as devised by WHO that proposes an interview about symptoms of TB. Suspects were asked to submit a spot sputum specimen for ZN smear and GeneXpert MTB Rif Assay simultaneously at the time chest radiograph. Results: A total of 545 index drug resistant TB patients were included for contact screening. A total of 2754 contacts with mean of 5.36±2.75 were verbally screened for tuberculosis using Baseline individual risk assessment questionnaire and a total 945 contacts were assessed for further investigation. Findings of x-ray suggesting any change in lungs of 7.1% contacts, smear positivity was found in 6.3% and GeneXpert MTB Rif Assay detected 9.8% of which 45.2% contacts were resistant to rifampicin. Conclusion: Active case detection of contacts is important in high burden settings while modern GeneXpert is a great addition in diagnostic tools and equally valuable in detection of TB among contacts and showed higher yield of MTB case detection as 37.6% over smear microscopy and 39.8% over X-ray.